EDUKASI ANTI BULLYING MELALUI SEMINAR “BE A BUDDY NOT A BULLY” BAGI SISWA SEKOLAH DASAR DI KAMPUNG BARU BANTEN - Millata Hanifa; Dirga Ayu Lestari; Farid Ma'ruf; Royhan Imamul Muttaqin; Kokom Komariah; Eem Komala (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying is a social problem that still frequently occurs in elementary schools and has the potential to negatively impact the psychological, emotional and social development of students. Students’ lack of understanding of the forms and impacts of bullying behavior often leads to bullying being considered part of normal interactions between friends. This community service activity aims to provide education about the dangers of bullying, instill empathy and mutual respect among students and increase student awareness so that they can protect their friends and not engage in bullying. The activity was carried out at SDN Kampung Baru, Serang Regency Banten, involving 71 elementary school students through a Participatory Action Research approach. The implementation method was carried out through an educational seminar "Be a Buddy Not a Bully" which included material delivery, educational video screenings, interactive discussions, simulations, questions and answers, ice breakers, and educational games. Data collection techniques were carried out through observation, structured interviews and pretests and posttests.